2014
DOI: 10.3329/jbsa.v22i2.18141
|View full text |Cite
|
Sign up to set email alerts
|

Use of labetalol and glyceryl trinitrate for induced hypotension in spine surgery- A comparative study

Abstract: Introduction:Anaesthesia may influence intraoperative bleeding in several ways both physiologically and pharmacologically. Elective hypotension is used to reduce operative blood loss especially in those operations like spine surgery 1 , middle ear surgery, cerebro-vascular surgery where even a small quantity of blood can obscure the operative field and make difficulties for the surgeon for a good proper surgery and prolong duration of operation 1 . Laryngoscopic stimulation of oropharyngeal structure may be an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One group received TNG, 1000 microgram, and the other group received labetalol, 5 mg, intravenously. They found a significantly higher score for surgical field quality and less bleeding in labetalol group ( 15 ). It is also interesting that they achieved these results with a much lower dose of labetalol as 5 mg.…”
Section: Discussionmentioning
confidence: 93%
“…One group received TNG, 1000 microgram, and the other group received labetalol, 5 mg, intravenously. They found a significantly higher score for surgical field quality and less bleeding in labetalol group ( 15 ). It is also interesting that they achieved these results with a much lower dose of labetalol as 5 mg.…”
Section: Discussionmentioning
confidence: 93%
“…Presynaptic alpha-2 receptors are spared by labetalol so that the released norepinephrine can continue to inhibit further release of catecholamines via the negative feedback mechanism resulting from the stimulation of alpha-1 receptors. Moreover this drug targets 5-10 times more specific beta blockade 11,23 and prevent rebound hypertension and tachycardia. 20,10 Researchers used Labetalol and nitroprusside to induce hypotension in major surgeries and showed that nitroprusside significantly increased the heart rate but cardiac output remain unchanged with labetalol administration.…”
Section: Discussionmentioning
confidence: 99%